THE INFLUENCE OF DIGITAL MARKETING ON TOURISM DESTINATION PROMOTION - I Gusti Made Riko Hendrajana; Sri Dewi Wahyundaru; Lucky Mochamad Kharisma; Komang S. M Parwati (Adisam Publisher, 2026)
The purpose of this study is to examine how digital marketing affects tourism destination promotion. In the increasingly developing digital era, traditional marketing has shifted, where digital marketing plays an increasingly important role in attracting tourists and building the image of tourist destinations. The study's findings demonstrate the substantial impact that digital marketing impact on increasing the exposure and reach of tourism destination promotion. Through social media, sponsored advertising, graphic content, and search engine optimization (SEO), tourist destinations are able to reach a wider and more targeted audience. In addition, digital marketing has also been proven to be able to improve the positive image of destinations through user reviews, influencer involvement, and interesting content. The application of technological tools like augmented reality and virtual tours provides a more interactive experience for potential tourists, thereby increasing the attractiveness of the destination. This study's conclusion is that digital marketing is a very effective tool in promoting tourist destinations, both in terms of costs and results obtained. The implementation of the right digital marketing strategy can help tourist destinations increase the number of visits, strengthen their image, and maintain competitiveness in the global tourism market.